A novel primary frequency regulation strategy of wind farm based on wind turbine health condition. Issue 10 (20th May 2022) - Li, Shaolin; Wang, Weisheng; Zhang, Xing; Qin, Shiyao; Ying, You
Abstract: In order to optimize the primary frequency regulation performance of the wind farm and increase the service life of the wind turbines (WTs), this paper presents a novel primary frequency regulation strategy of the wind farm to maintain the system frequency considering each WT's health condition level. The proposed strategy can make WTs participate in frequency regulation according to their health conditions. Thus, the unhealthy WTs can be prevented from further deteriorating by reducing the load. In this paper, condition monitoring data from WTs is applied to estimate their health condition levels. Then, the power support is estimated according to the supplementary loop which includes inertial control and droop control. An adaptive model predictive control (AMPC) algorithm is employed to improve the control accuracy and mitigate the fluctuation caused by frequency variation. The case study is carried out in a two‐area wind‐diesel power system to validate the effectiveness of the proposed method. The results show that the proposed strategy optimizes the effect of primary frequency regulation while reducing the load on unhealthy WTs.